Compositional and Tribo‐Mechanical Characterization of Ti‐Ta Coatings Prepared by Confocal Dual Magnetron Co‐Sputtering. Issue 3 (2nd November 2017) - Bahrami, Amin; Álvarez, Jonatán Pérez; Depablos‐Rivera, Osmary; Mirabal‐Rojas, Roberto; Ruíz‐Ramírez, Agustin; Muhl, Stephen; Rodil, Sandra E.
Abstract : Titanium‐Tantalum coatings are deposited by magnetron co‐sputtering technique, using independently driven titanium and tantalum targets. The effect of the Ta content on the structure, mechanical, and wear properties of Ti films i s investigated . It is found that the percentage of the added Ta varies linearly from 3.7 to 31.3 at% by increasing the power applied to the Ta target from 10 to 100 W. The XRD results show that the coatings are crystalline, and there is no evidence of the formation of intermetallic phases, instead formation of metastable phases of α ″ and β depending on Ta content are observed, though the samples are deposited at low temperature (150 °C). It is shown that the elastic strain to failure ( H / Er ; hardness to reduced elastic moduli ratio) can be increased by 40% through the formation of crystalline phases with a lower E, while the hardness remains constant. The tribological study shows that increasing the Ta content up to 14.9 at% causes a significant improvement in adhesion of the coating to a soft metallic substrate. Abstract : The production of nanostructured, hard, and tough metallic coatings using vapor deposition method is of increasing interests in the coating of metallic substrates. The results in this study show that addition of Ta to the Ti coatings improves the toughness and adhesion of coatings to the substrate, although it has not significant effect on the hardness of coatings.